Self-esteem development in early adolescence: an application of the latent change variable models - Buško, Vesna (Array, 2013)
The developmental changes in general self-esteem were analyzed on a sample of 309 seventh and eight grade primary school participants of both sexes. The data on the general self-esteem were collected in the preadolescent sample on four occasions of measurement within the two year period. Following the assumptions of the latent state-trait theory (LST ; Steyer et al., 1999), the measurement models were defined to represent the degree to which variations in self-esteem measures were due to individual dispositions and/or to occasion-related influences. Further, the models of LST theory were specified to include the latent variables corresponding to the state variability and the trait change in self-esteem scores. By use of the true intraindividual change modeling procedures, the identified latent change variables were found to be related to students' engagements in sports and to a lesser extent to their academic achievement.